Zakażenia narządów płciowych u dziewcząt - profilaktyka i leczenie - Drosdzol-Cop, Agnieszka; Białka, Agnieszka; Bakon, Igor; Skrzypulec-Plinta, Violetta (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Genital infections are a frequent diagnosis in pediatric and adolescent gynecology outpatient clinics, 2/5 of which relate to girls aged 0-14 years. The course of disease ranging from symptoms and ending on the treatment depends on many factors, foremost of the infection pathogen, but also on the child’s age, coexisting diseases and sexual activity. Genital infections in girls can be caused by bacteria, viruses, fungi, parasites or factors of non-communicable. The most common symptoms of vulvovaginitis in girls are vaginal discharges with different color, texture and smell, occurring in 60-90% of the cases. Diagnosis of genital infections should begin with an anamnesis. During gynecological examination of external sexual organs, the vestibule of the vagina, urethra and area around the anus should be revealed for the presence of skin lesions and absences of the defects of interior genital. In sexually active girls cervix and vaginal walls should be also revealed. Personal hygiene and supportive treatment (sitz baths, vaginal irrigation, topical soothing agents, corticosteroids, antihistamines, loose cotton underwear, preparations of lactic acid) play a huge role in the prevention of vulvovaginitis in girls. Treatment of infections should be based on the result of bacteriological testing and antibiogram, in dose adjusted to age and body weight of girl.